2018
DOI: 10.1016/j.pld.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The first complete plastid genome of Burmannia disticha L. from the mycoheterotrophic monocot family Burmanniaceae

Abstract: Burmanniaceae is one major group within the monocot order Dioscoreales that has not had its plastome sequenced. Members of Burmanniaceae are mostly achlorophyllous, although the genus Burmannia also includes autotrophs. Here, we report sequencing and analysis of the first Burmanniaceae plastid genome from Burmannia disticha L.. This plastome is 157,480 bp and was assembled as a circular sequence with the typical quadripartite structure of plant plastid genomes. This plastome has a regular number of potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…As shown in the previous studies, our comparison also confirmed that the IR region was more conserved than the LSC and SSC regions within these species ( Fig. 3; Zhao et al, 2018;Ma et al, 2018).…”
Section: Comparative Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…As shown in the previous studies, our comparison also confirmed that the IR region was more conserved than the LSC and SSC regions within these species ( Fig. 3; Zhao et al, 2018;Ma et al, 2018).…”
Section: Comparative Analysissupporting
confidence: 89%
“…The intron and intergenic spacer region covered 36.1% of the genome (intron 7%, and intergenic spacer 29%). Overall guanine-cytosine (GC) content of T. zeylanicus chloroplast genome was 37.24% which is similar to closely related species (Zhao et al, 2018;Ma et al, 2018). The GC contents of the LSC and SSC regions are 31.5% and 31.4%, respectively, whereas that of the IR regions is 42.2%.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…Burmannia contains about 60 species spanning from autotrophic, hemi-mycoheterotrophic to mycoheterotrophic (Jonker 1938;Zhang 1999;Wu et al 2010), which could provide an excellent model system for understanding the evolution of plastome responding to the lifestyle shift from autotrophic to heterotrophic. Although the plastome of autotrophic Burmannia disticha (Ma et al 2018) has been described, the plastome of mycoheterotrophic species in Burmannia has never been reported, hindering our efforts in elucidation of plastid evolution in the genus. Aiming to provide new evidence in our understanding of the mechanism of plastid evolution in mycoheterotrophic angiosperms, here we focus on Burmannia itoana, a mycoheterotrophic perennial herb ( Fig.…”
Section: Introductionmentioning
confidence: 99%